Późnolakońska nazwa rzepy - Elwira Kaczyńska (Ksiegarnia Akademicka Publishing, 2019)
Late Laconian Name for ‘Turnip’ In his work Deipnosophistae (IX 369b), Athenaeus discusses Greek names for ‘turnip’, including Laconian γάστρα and Boeotian ζεκελτίς. Hesychius of Alexandria (5th c. AD) gives two Late Laconian names: γασταία and θικέλιν (‘turnip, Brassica campestris L., syn. Brassica rapa L.’). The former term is an obvious reflex of Lac. γάστρα, while the latter seems to be a dialectal innovation. The present authors suggest that Late Laconian θικέλιν ‘turnip’ (originally ‘small gourd’) represents a diminutive form, derived from Late Laconian *θιᾱ́ f. ‘bottle gourd, Lagenaria siceraria (Molina) Standl’ (= Tsakonian θιάα, θιᾶ [θiˈa] f. ‘bottle, flask; gourd / φιάλη; νεροκολόκυθο’ < Gk. Lac. φιάλᾱ ‘id.’, cf. Attic-Ionic φιάλη f. ‘a broad, flat vessel; bowl for drinking’) by means of the diminutive suffix *-κέλ(λ)ιον (< Latin -cellum). Ancient Greeks used the same name to denote turnips and bottle gourds, see the Hesychian gloss ζακελτίδες· κολοκύνται ἢ γογγυλίδες (‘bottle gourds or turnips’). Athenaeus (IX 369b) gives an analogous pair of lexical correspondences: Boeotian ζεsκελτίδες ‘turnips’ and Thessalian (?) ζακελτίδες ‘bottle gourds’.